What is democracy? - Touraine, Alain (Westview Press, 1997)
In this sequel to A Critique of Modernity, Alain Touraine questions the social and cultural content of democracy today. At a time when state power is being increasingly eroded by the economic might of transnational capital, what possible value can we ascribe to a democratic idea that is defined merely as a set of guarantees against the totalitarian state?If democracy is to survive in the postcommunist world, Touraine argues, it must accomplish two urgent goals: It must somehow protect the power of the nation-state at the same time as it limits that power (for only the state has sufficient means to counterbalance the global corporate wielders of money and information); and it must reconcile social diversity with social unity and individual liberty with integration.This is not merely a philosophical problem but a dilemma whose resolution will dramatically affect the immediate future of people everywhere. If we want a resolution in democracy's favor, then it is time, in Touraine's view, for us to redefine democracy in terms of active intervention rather than mere passive institution. To preserve the power and effectiveness of our states and societies, we must make visible strides-and soon-away from a politics of particularity and toward the integration and balancing of women and minorities, of immigrants, of rich and poor. If our states become too weakened, too debased by the politics of competing identities and interest groups, we will one day find ourselves without the means to protect the very values we believe we are fighting to uphold.